1999
DOI: 10.1080/10715769900300501
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic liver ischemia and antioxidant treatment during hepatic resections

Abstract: The purpose of our study was to evaluate the clinical impact of reperfusion injury after normothermic ischemia during major liver resections and the effect of an intraoperative antioxidant infusion. This prospective randomized study comprised 50 patients; half of them (treatment group) were given an antioxidant infusion containing tocopherol and ascorbate immediately prior to reperfusion onset. Venous blood samples for the determination of MDA-TBARS (malondialdehyde-thiobarbituric acid reactive substances) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…In a pilot clinical study, Biasi et al concluded that administration of an antioxidant supplement containing vitamins E and C during the period of warm ischemia and during the first 30 minutes of reperfusion in patients undergoing liver transplantation, significantly reduced indices of oxidative stress and neutrophil activation during the first hours of reperfusion [123]. Similarly, protective effects offered by the combination of these antioxidants have been demonstrated in other studies [124].…”
Section: Vitamins E and Cmentioning
confidence: 95%
“…In a pilot clinical study, Biasi et al concluded that administration of an antioxidant supplement containing vitamins E and C during the period of warm ischemia and during the first 30 minutes of reperfusion in patients undergoing liver transplantation, significantly reduced indices of oxidative stress and neutrophil activation during the first hours of reperfusion [123]. Similarly, protective effects offered by the combination of these antioxidants have been demonstrated in other studies [124].…”
Section: Vitamins E and Cmentioning
confidence: 95%
“…Portal triad occlusion performed in rats also increased serum MDA levels, which peaked at day 4 after the operation [21]. Cerwenka et al [22] measured MDA-TBARS levels during major liver resection and found that they were increased after liver ischemia, but that the effect was smaller or even absent in patients with advanced cirrhosis. They also suggested that this increase could be reduced by intraoperative administration of an antioxidant infusion [22].…”
Section: Discussionmentioning
confidence: 98%
“…In order to assess lipid peroxidation, MDA and TBARS have been determined in various pathological conditions (Abou-Seif and Youssef, 2001;Arnalich et al, 2001;Templar et al, 1999;Naveau et al, 2001;Schisterman et al, 2001;Elis et al, 2001;Cerwenka et al, 1999). Likewise, numerous studies, including animal models (Hsiang et al, 1997) and clinical trials (Karakuecuek et al, 1997;Kasprzak et al, 2001;Bochicchio et al, 1990;Cernak et al, 2000), have attempted to mea-LIPID PEROXIDATION EARLY AFTER BRAIN INJURY 671 Pupils, percentage of patients with at least one pupil dilated and nonreactive; GCS, Glasgow Coma Scale; ICP 1, highest intracranial pressure reading on admission; ICP2, highest intracranial pressure reading during mesurement of markers.…”
Section: Discussionmentioning
confidence: 99%